PEMBENTUKAN KECERDASAN EMOSI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA PESERTA DIDIK KELAS XI IPA 2 DI MAN KLATEN TAHUN PELAJARAN 2022/2023 - Shafa Alistiana Irbathy (MAMBA'UL 'ULUM, 2023)
Intellectual intelligence (IQ) and emotional intelligence (EQ) play an important role in success, keep in mind that intellectual intelligence (IQ) and emotional intelligence (EQ) alone do not guarantee success and happiness and both must be in balance with spiritual intelligence. If not, it will affect the mental and psychological development of students, making them alienated from God. Common problems faced by students during personality formation are managing communication and behavior in the social environment, especially in terms of emotional intelligence, students cannot control their emotions, are too sensitive, selfish, tend to do bad things, are easily influenced, ambitious and doubtful. Most problems arise when religious education does not have an impact on character formation, so students do not have a basis for social life, and experience physical and mental imbalance. So Islamic education is needed as a mean to gain access and control the behavior of all students, whether deviant or not, so that students are able to control their behavior so as to form individuals based on religious teachings. The aim of this research is to find out aspects in Islamic Education that can shape students' emotional intelligence. This research used a qualitative approach with a descriptive qualitative type and used observation, interviews and documentation as data collection procedures. The results of this research in forming students' emotional intelligence require aspects of self-awareness, self-regulation, teaching social skills and empathy for students. These results provide implications that arise from emotional intelligence which influences students' personal and social adjustment. In learning, Islamic Education requires adjustments so that students become "adults" in facing their environment, so this emotion adds a sense of enjoyment to everyday experiences.